The Science of Salt: A global review on changes in sodium levels in foods. Issue 8 (13th July 2019) - Santos, Joseph Alvin; Sparks, Emalie; Thout, Sudhir Raj; McKenzie, Briar; Trieu, Kathy; Hoek, Annet; Johnson, Claire; McLean, Rachael; Arcand, JoAnne; Campbell, Norman R. C.; Webster, Jacqui
Abstract: This review aims to summarize and synthesize studies reporting on changes in sodium levels in packaged food products, restaurant foods, and hospital or school meals, as a result of salt reduction interventions. Studies were extracted from those published in the Science of Salt Weekly between June 2013 and February 2018. Twenty‐four studies were identified: 17 assessed the changes in packaged foods, four in restaurant foods, two in hospital or school meals, and one in both packaged and restaurant foods. Three types of interventions were evaluated as part of the studies: voluntary reductions (including targets), labeling, and interventions in institutional settings. Decreases in sodium were observed in all studies (n = 8) that included the same packaged foods matched at two time points, and in the studies carried out in hospitals and schools. However, there was little to no change in mean sodium levels in restaurant foods. The pooled analysis of change in sodium levels in packaged foods showed a decrease in sodium in unmatched food products (−36 mg/100 g, 95% CI −51 to −20 mg/100 g) and in five food categories—breakfast cereals, breads, processed meats, crisps and snacks, and soups. Twenty‐two of the 24 studies were from high‐income countries, limiting the applicability of the findings to lower resource settings.